Protagonismo e empoderamento feminino nos filmes de super-heroínas: uma análise dos filmes "Mulher-Maravilha" e "Capitã Marvel" - Juliana Pieve de Souza (2021)
The releases of the movies Wonder Woman (Petty Jenkins, 2017) and Captain Marvel (Anna Boden, Ryan Fleck, 2019) arouse an enormous expectation for being the first of the so-called DC Extended Universe and Marvel Cinematographic Universe to feature superheroines as protagonists. Understanding cinema as an important leisure experience, which may collaborate in the construction of other perspectives about the world, the present study aimed to investigate how the protagonist role of the characters Diana and Carol Danvers was developed in the films Wonder Woman and Captain Marvel respectively, through narratives and cinematographic language. It also aimed to understand to what extent possibilities of empowerment in these films were made effective for them. In order to carry out this investigation, bibliographic research and film analysis were used as methods, based on the proposals of authors Laurent Jullier and Michel Marie, contained in the book “Lendo as imagens do cinema”. It was found that strategies to reaffirm Diana's protagonism were based on the narrative, on her physical appearance and on her constant presence on screen, represented most of the time, in a sensual way. As for the character Carol Danvers, the main strategies that reaffirmed her protagonism focused on the narrative and on camera positions, which worked in favor of bringing the viewer closer to the character's subjectivity. As for empowerment, mainly from a feminist perspective, which has as its main objective the breaking of the precepts of patriarchy, the data obtained showed that for Diana, the matter of empowerment was not confirmed, while for Carol, some possibilities were built. The results of the analyzes showed that these movies contribute for strengthening women representation within the movie gender they are inserted. However, the patriarchal logic still persists in the narrative of Wonder Woman and in the physical construction of both characters.